The Transformation of Islamic Education Delivery Methods: From Classical Traditions to Contemporary Pedagogical Approaches - Damayanti, Ina; Sultan; Paewai, Rusman (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
This article aims to analyze the transformation of instructional methods in Islamic education from classical traditions to contemporary pedagogical approaches. The study is motivated by the need for methodological renewal in Islamic education that responds to social changes and developments in modern learning theories. This research employs a qualitative approach through library research, using critical analysis of classical and contemporary literature related to Islamic educational methodology.nThe findings reveal that during the classical period, instructional methods in Islamic education were predominantly characterized by oral transmission, memorization, and written scholarship, emphasizing knowledge transmission and scholarly authority. In contrast, contemporary Islamic pedagogy demonstrates a shift toward participatory, dialogical, and contextual approaches, including discussion, demonstration, experimentation, project-based learning, as well as the reinforcement of role modeling and habituation as instruments for character formation. This transformation does not represent a discontinuity but rather reflects a continuity of foundational values integrated with methodological innovation. The study concludes that the development of instructional methods in Islamic education should integrate classical epistemological heritage with modern pedagogical principles to remain relevant, adaptive, and effective in fostering both intellectual competence and spiritual character among learners.